2015
DOI: 10.5935/abc.20150070
|View full text |Cite
|
Sign up to set email alerts
|

Effects of One Resistance Exercise Session on Vascular Smooth Muscle of Hypertensive Rats

Abstract: BackgroundHypertension is a public health problem and increases the incidence of cardiovascular diseases.ObjectiveTo evaluate the effects of a resistance exercise session on the contractile and relaxing mechanisms of vascular smooth muscle in mesenteric arteries of NG-nitro L-arginine methyl ester (L-NAME)-induced hypertensive rats.MethodsWistar rats were divided into three groups: control (C), hypertensive (H), and exercised hypertensive (EH). Hypertension was induced by administration of 20 mg/kg of L-NAME f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, the role of resistance exercise has been evaluated in the prevention and treatment of several cardiovascular diseases. 20 , 22 However, although the majority of the studies focus on the vascular effects of aerobic exercise, our data are the first that demonstrate the volume-dependent effect on vascular adaptations after a single bout of resistance exercise. Finally, the current findings may contribute to the establishment of safe limits of exercise for patients with endothelial dysfunction and insulin resistance.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Furthermore, the role of resistance exercise has been evaluated in the prevention and treatment of several cardiovascular diseases. 20 , 22 However, although the majority of the studies focus on the vascular effects of aerobic exercise, our data are the first that demonstrate the volume-dependent effect on vascular adaptations after a single bout of resistance exercise. Finally, the current findings may contribute to the establishment of safe limits of exercise for patients with endothelial dysfunction and insulin resistance.…”
Section: Discussionmentioning
confidence: 76%
“…Several studies using a single bout of aerobic 19 or resistance 20 , 21 exercise observed an enhanced vascular relaxation, suggesting an increased NO bioavailability after a session of exercise. Furthermore, the role of resistance exercise has been evaluated in the prevention and treatment of several cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…There is lack of evidence regarding the effects of resistance exercise on endothelialindependent function. Animal research in N G -nitro-L-arginine-methyl-ester (L-NAME)induced hypertensive rats demonstrated that one resistance exercise session resulted in a reduction in the potassium chloride (KCI)-induced contracting mechanisms by enhancing the vasodilatory sensitivity of the mesenteric artery smooth muscle (Silva et al, 2015). Rats that underwent a resistance exercise session had a reduction in contraction in response to depolarising KCI solutions.…”
Section: Endothelial-independent Functionmentioning
confidence: 99%